Hanhart syndrome: A rare case report and review of literature - Das, Shreya; Mazumdar, Anjana; Maity, Bikash Chandra; Ghose, Sandip (Indian Journal of Case Reports, 2019)
Hanhart syndrome is a rare congenital and genetic disease, in which the most common signs are short, incompletely developed tongue (hypoglossia), absent or partially missing fingers and/or toes (hypodactylia), malformed arms and/or legs (peromelia), and small jaw (micrognathia). Here, we report a case of Hanhart syndrome in an 18-year-old boy. The boy presented with few extraoral and intraoral abnormalities such as short toes and phalanges along with partial syndactyly in the left hand only were the most relevant. Other features such as micro and retrognathic face, incompetent lips, and wide nasal bridge were also significant. The boy was suffering for difficulties in speech and swallowing due to small tongue size, high arched palate, crowding, and few missing teeth. To provide adequate treatment to a patient with Hanhart syndrome, this study aimed to review and to analyze this literature and treatment protocols.